2015
DOI: 10.1039/c4cc06824f
|View full text |Cite
|
Sign up to set email alerts
|

Probing structural changes of self assembled i-motif DNA

Abstract: We report an i-motif structural probing system based on Thioflavin T (ThT) as a fluorescent sensor. This probe can discriminate the structural changes of RET and Rb i-motif sequences according to pH change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 53 publications
2
35
0
Order By: Relevance
“…59 At present, the G-quadruplex specific ThT has attracted increasing interests, and it has been used as a light-up fluorescence probe for the sensing of the G-quadruplex, biothiols, Hg 2+ , K + , liver-related short gene, and the structure change of i-moif. [60][61][62][63][64][65] Inspired by these studies, we constructed a new FRET system using CP as an donor and ThT as an acceptor, and designed a simple, label-free, and sensitive biosensor for the detection of thrombin in buffer and in diluted serum. An improved sensitivity for thrombin detection was obtained when compared with two recent strategies based on the FRET from the CP to the dye.…”
mentioning
confidence: 99%
“…59 At present, the G-quadruplex specific ThT has attracted increasing interests, and it has been used as a light-up fluorescence probe for the sensing of the G-quadruplex, biothiols, Hg 2+ , K + , liver-related short gene, and the structure change of i-moif. [60][61][62][63][64][65] Inspired by these studies, we constructed a new FRET system using CP as an donor and ThT as an acceptor, and designed a simple, label-free, and sensitive biosensor for the detection of thrombin in buffer and in diluted serum. An improved sensitivity for thrombin detection was obtained when compared with two recent strategies based on the FRET from the CP to the dye.…”
mentioning
confidence: 99%
“…The i-motif structure can be induced and consolidated by a slightly acidic pH (protonation of the N3 in cytosine) or Ag + at neutralp H( formation of C-Ag + -C), so that basic logic gates could be easily operated by inputting ap Hm odulated factor or Ag + affinity agents, such as cysteineo rh alide ions. Similar to G-quadruplexes, many fluorescent dyes have been reported that have the capability of binding i-motif with enhanced luminescent signals,s uch as [Ru(phen) 2 (dppz)] 2 + , [80] crystal violet, [81] ThT, [82] cyanine dye DMSB, [83] thiazole orange (TO), [84] and berberine, [85] which provide i-motif-based circuits with detectable outputs. [86] For instance, Ta ng et al [87] designed aC -rich strand to realize OR and INHIBIT functions by employing Ag + /H + and Ag + /I À as the inputs, respectively and DMSB as the signal actuator.L uo et al [84b] took TO as i-motif monitor and Ag + /cysteine as inputs to operate an INHIBIT gate.…”
Section: Signalwith the Help Of I-motifmentioning
confidence: 99%
“…In 2015, ThT was employed as fluorescence sensor for detection of imotif in retinoblastoma (Rb) and RET proto-oncogene using CD spectroscopy and fluorescence studies at different pH values. It was found that ThT acted as an efficient sensor to probe the conformational changes in i-motifs by the virtue of its high degree of sensitivity towards changes in its local microenvironment (Lee et al, 2015).…”
Section: Thioflavin-t: Nucleic Acid Sensormentioning
confidence: 99%